Extending your SOA for Intercompany Integration find you own value. - Linthicum, David S.
Service oriented architecture, or SOA, is the modern notion of connecting systems together at both the information and service levels. Indeed, enterprises are racing to enable their existing applications to externalize services, as well as build the appropriate integration infrastructure around it.